Ceremonial Economics: A General Review - YOLUSEVER, ARAS (İstanbul Üniversitesi, 2024)
Ceremonial economics explores how traditional values, myths, and rituals intersect with economic practices and institutions. It differentiates between "ceremonial" practices based on tradition and cultural values and "instrumental" practices based on efficiency and problem-solving capabilities. This field, rooted in institutional economics, emphasizes the tension between preserving established social orders and fostering innovation. Scholars can gain insights into the broader implications of economic systems by understanding how ceremonial practices influence economic behavior and social cohesion. This pluralistic approach comprehensively analyzes how ceremonial and instrumental practices interact within various economic systems. The main goal of this study is to develop a detailed and all-encompassing framework for ceremonial economics. A key aspect of this will involve comparing ceremonial economics principles with institutional economics. Additionally, the study will delve into various aspects of ceremonial economics, specifically focusing on cultural and social aspects. Furthermore, the study conducts four examples to provide practical insights into the application of ceremonial economics.
Keywords: Ceremonial Economics; Institutional Economics; Rituals; Economic Practices